Simulation of turbulent boundary layer with negative pressure gradient - Мовчан, В. Т.; Романюк, Л. А. (Proceedings of National Aviation University (archive), 1998)
Proposed is mathematical model and approximate analytical solutions for turbulent boundary flows with negative pressure gradient. The mathematical model and approximate solution are aimed at direct use as well as in digital calculation method which is necessary for designing and construction of various machines, installations and technological processes